Analisis kesalahan berbahasa pada karangan deskripsi peserta didik kelas iv sekolah dasar - Fadhilah, Siti; Slamet, St. Y; Atmojo, Idam Ragil Widianto (Didaktika Dwija Indria, 2025)
This research aims to: (1) describe the forms of language errors found in the descriptive essays of fourth grade students at SDN 1 Cepedak for the 2023/2024 academic year, (2) describe the factors that cause language errors in students' descriptive essays, and (3) describe the teacher's efforts to overcome language errors that occur in students' descriptive essays.This research is a qualitative descriptive research with a case study approach. The data sources for this research include offline learning activities, informants (grade IV teachers and fourth grade students), and documents (students' descriptive essays). Data collection was carried out using passive participant observation techniques, in-depth interviews with teachers and students, and document analysis. The data validity testing techniques used are source triangulation and technical triangulation.The results of this research are as follows. First, errors in the use of letters are the category of errors that are most often found and errors in writing absorption elements are the errors that are made the least by students. Second, the cause of these errors is students' lack of understanding of language rules. Teachers also have not used strategies or media to support writing learning activities in their classes. The teacher's effort to overcome this problem is by holding activities that involve composition skills regularly so that students get used to writing essays. Teachers also provide direct direction to students when they find errors in students' writing.